2016
DOI: 10.1080/13611267.2016.1170561
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring as Socialization for the Educational Leadership Professoriate: A Collaborative Autoethnography

Abstract: In this study, we analyzed the experiences of an educational leadership doctoral student and aspirant to the professoriate (protégé) and an educational leadership professor (mentor) during our two-year mentoring relationship. Collaborative autoethnography was employed, and our analysis relied primarily upon a processoriented model of mentoring. Four main themes emerged: (a) reciprocal trust, (b) experiential learning, (c) stability and change, and (d) mutual benefit. Our relationship also was marked by several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Through frequent interaction, a positive nature, and being centered on positive concern for another, mentoring, particularly for scholarpractitioners in Ed.D. programs, can provide the socialization needed for academic success (Allen & Eby, 2007;Malin & Hackmann, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Through frequent interaction, a positive nature, and being centered on positive concern for another, mentoring, particularly for scholarpractitioners in Ed.D. programs, can provide the socialization needed for academic success (Allen & Eby, 2007;Malin & Hackmann, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Few studies addressing the educational leadership professoriate have been conducted (Malin & Hackmann, 2016;Mansfield, Welton, Lee, & Young, 2010), with mentoring often "conceptualized narrowly by being limited to technical supervising and advising" for dissertation completion (K. Young & Harris, 2012, p. 343). Mentoring research for the educational leadership professoriate primarily has focused on women's or underrepresented students' experiences (Kottkamp & Rusch, 2009).…”
Section: Mentoring Within Higher Education and Educational Leadershipmentioning
confidence: 99%
“…Quality mentoring was essential: Students valued professors who willingly met to provide guidance, perceiving they were "in a better position to navigate the university structure, demands, and requirements" (p. 45). Malin and Hackmann (2016) analyzed their successful student-professor mentoring relationship using collaborative autoethnography. They developed four main themes-reciprocal trust, experiential learning, stability and change, and mutual benefit-and noted several critical relational features.…”
Section: Mentoring Within Higher Education and Educational Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheung, Reinhardt, Stone, Little (2018) devised the Science Teacher Leader Profile, it involves four main activities including the modelling effective instruction. Based on the analysis of the perception of educational leadership by doctoral students and PhD students of the professoriate and an educational leadership professor (mentor) Malin and Hackmann (2016) considered and detailed the model of mentoring. Zacher and Johnson (2015) indicated that PhD students' perception of their professors as transformational leaders positively correlates with the ratings of professors' creativity.…”
Section: Introductionmentioning
confidence: 99%